From viral videos to virtual sales: understanding TikTok Shop - Amirrudin, Faizatul Akmam; Ahmad Jamil, Norina (Universiti Teknologi MARA, Terengganu, 2024)
TikTok Shop is an e-commerce platform integrated into TikTok Shop is an innovative social commerce feature and integrated into the popular social media app TikTok. It allows users to discover and purchase products directly through the app, enhancing the social commerce experience by blending entertainment with shopping, creating a unique and seamless shopping experience for users. Launched in November 2022, the feature enables users interested in starting a business and generating income to upload their curated products on TikTok, aiming to revolutionize the way consumers discover and purchase products online.